Species coherence in the face of karyotype diversification in holocentric organisms: the case of a cytogenetically variable sedge (Carex scoparia, Cyperaceae) - Escudero, Marcial (Oxford University Press, 2013)
BACKGROUND AND AIMS: The sedge genus Carex, the most diversified angiosperm genus of the northern temperate zone, is renowned for its holocentric chromosomes and karyotype variability. The genus exhibits high variation in chromosome numbers both among and within species. Despite the possibility that this chromosome evolution may play a role in the high species diversity of Carex, population-level patterns of molecular and cytogenetic differentiation in the genus have not been extensively studied. METHODS: Microsatellite variation (11 loci, 461 individuals) and chromosomal diversity (82 individuals) were investigated in 22 Midwestern populations of the North American sedge Carex scoparia and two Northeastern populations. KEY RESULTS: Among Midwestern populations, geographic distance is the most important predictor of genetic differentiation. Within populations, inbreeding is high and chromosome variation explains a significant component of genetic differentiation. Infrequent dispersal among populations separated by >100 km explains an important component of molecular genetic and cytogenetic diversity within populations. However, karyotype variation and correlation between genetic and chromosomal variation persist within populations even when putative migrants based on genetic data are excluded. CONCLUSIONS: These findings demonstrate dispersal and genetic connectivity among widespread populations that differ in chromosome numbers, explaining the phenomenon of genetic coherence in this karyotypically diverse sedge species. More generally, the study suggests that traditional sedge taxonomic boundaries demarcate good species even when those species encompass a high range of chromosomal diversity. This finding is important evidence as we work to document the limits and drivers of biodiversity in one of the world's largest angiosperm genera.